O fortalecimento da capacidade de resiliência como fator de superação de traumas na comunidade carente - Batista, Raquel Barbosa de Mesquita (2023)
This dissertation work was carried out at the Pontifical Catholic University of São Paulo - PUCSP to obtain the Master's degree in Clinical Psychology. Based on the hypothesis that overcoming trauma in adolescents living in poor communities depends on strengthening their resilience, he elaborated the following research questions: What is the sociocultural reality of the investigated subjects and their relationship with possible psychological traumas? What difficulties did you face in overcoming them? What resilience factors helped the subjects in their search for overcoming? The general objective was to study the overcoming of traumas in adolescents, residents of the poor community, in order to discover a possible relationship with the development of resilience capacity, considering the following specifics: to contextualize the chosen community within the social scope based on the results of the interviews with adult residents (community leaders, teachers and AACA founders); to describe the changes made to the community's timeline, considering the before and after of the actions of community leaders; to discover the traumas and their triggering events in the interviewed adolescents; to analyze the subjectivity of trauma patients; to consider the profile of a resilient person, in view of the meaning they give their life in that community; to distinguish, in the analysands, the factors that promote resilience; consider the relationship between psychoanalysis and resilience based on the studies carried out. The method used in the analyzes was qualitative, which is “fundamentally interpretive”. As for the theoretical proposal, some aspects of Freud's proposal (regarding psychic protection devices) and some neo-Freudians stand out, especially with regard to psychological trauma and its relationship with the social events that caused it. In addition, authors such as Edith Henderson Grotberg, Aldo Melillo, Elbio Néstor Suárez Ojeta who developed works on resilience, considering the factors that promote it, were studied. The research site was the AACA Child and Adolescent Support Association, located in the poor community Ilha Santa Terezinha in Recife-PE. It consists of six chapters distributed as follows: Theoretical review: Resilience and Psychoanalysis; Corpus approach methodology; Santa Teresinha Island; Traumacausing events; The psychological trauma; Resilience: the strength that overcomes traumas. It was observed that, even living in a vulnerable environment such as Ilha Santa Teresinha, the interviewees are resilient and manage to overcome numerous difficulties and have a positive expectation of life with many dreams for the future. AACA provides that strength to overcome adversity. When they are there, they forget the problems they face at home or in the community and make their choices for the future with the learning of teachers and staff. A resilient school forms resilient students